Method for preparing solid electrolyte and solid electrolyte

By adding trace amounts of low-polar or non-polar solvent to the sulfide-based solid electrolyte precursor, the problem of adhesion and uneven mixing of sulfide-based solid electrolyte during the preparation process is solved, and a solid electrolyte with high yield and excellent performance is achieved.

CN119631215APending Publication Date: 2025-03-14LG CHEM LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380059544.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the preparation process, sulfide-based solid electrolytes are prone to react with moisture in the air to produce harmful gas hydrogen sulfide, and are prone to problems of precursor adhesion and uneven mixing, resulting in reduced yield and poor performance.

Method used

By adding trace amounts of low-polar or non-polar solvent to the sulfide-based solid electrolyte precursor, the precursor adheres and prevents uneven mixing, thereby improving the yield and performance of the sulfide-based solid electrolyte.

Benefits of technology

It effectively prevents the generation of hydrogen sulfide gas, improves the yield and ion conductivity of solid electrolytes, reduces electron conductivity, and improves the performance characteristics of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119631215A_ABST
    Figure CN119631215A_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a solid electrolyte, the method comprising a step (S1) of preparing a precursor mixture by mixing a sulfide-based solid electrolyte raw material and a solvent having a relative polarity with respect to water of 0.15 or less, and a step (S2) of heat-treating the precursor mixture, and the amount of the solvent is greater than 2% by weight and less than or equal to 5% by weight, based on the total amount of the precursor mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0117224, filed on September 16, 2022, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a method for preparing a solid electrolyte, which can prevent adhesion of a sulfide-based solid electrolyte precursor and prevent uneven mixing, and the solid electrolyte. Background Art

[0004] All-solid-state batteries are batteries that replace the liquid electrolyte filled between the positive and negative electrodes of conventional lithium secondary batteries with solid batteries. Among them, they are safe because there is no risk of explosion, and their energy density is higher than that of conventional batteries, so they have attracted attention as the next generation of batteries. The solid electrolyte used in all-solid-state batteries is a solid material that can conduct lithium ions in the battery, wherein its high ion conductivity is comparable to the electrolyte currently used in lithium secondary batteries. The core materials constituting the solid electrolyte include polymers, sulfides or oxides, but among them, sulfide-based solid electrolytes with high ductility and ion conductivity are evaluated as suitable for preparing large batteries with high capacity.

[0005] However, since sulfide-based solid electrolytes are highly reactive to moisture, they have a problem in that they react with moisture in the air to produce harmful gas hydrogen sulfide. Therefore, the toxic hydrogen sulfide may not only have an adverse effect on worker safety, but also reduce the ionic conductivity of the sulfide-based solid electrolyte itself.

[0006] Furthermore, in the case of dry mixing to synthesize conventional sulfide solid electrolytes, there may be a problem in which the precursor adheres to the container, causing uneven mixing while reducing the electrolyte yield, while in the case of wet mixing by adding a large amount of solvent, the adhesion of the precursor can be prevented, but there is a problem in that the final product has a relatively high electronic conductivity and therefore may not function like a normal solid electrolyte.

[0007] (Patent Document 001) KR 2018-0057423 A Summary of the invention

[0008] Technical issues

[0009] One aspect of the present invention provides a method for preparing a solid electrolyte, which improves the yield of the sulfide-based solid electrolyte by adding a trace amount of a low-polarity or non-polar solvent to a sulfide-based solid electrolyte precursor to prevent precursor adhesion and prevent uneven mixing.

[0010] Another aspect of the present invention provides a solid electrolyte in which solid electrolyte precursors are uniformly mixed to reduce the amount of unreacted or side-reacted impurities, increase ion conductivity, and simultaneously reduce electronic conductivity.

[0011] Technical Solution

[0012] The present invention provides a method for preparing a solid electrolyte and the solid electrolyte.

[0013] (1) The present invention provides a method for preparing a solid electrolyte, the method comprising a step (S1) of preparing a precursor mixture by mixing a sulfide solid electrolyte raw material and a solvent, and a step (S2) of heat treating the precursor mixture, wherein the relative polarity of the solvent to water is less than 0.15, and the amount of the solvent is greater than 2 wt% and less than or equal to 5 wt% based on the total amount of the precursor mixture.

[0014] (2) The present invention provides the method of (1) above, wherein the dielectric constant of the solvent is 4.0 or less.

[0015] (3) The present invention provides the method of (1) or (2) above, wherein the solvent is at least one selected from the group consisting of xylene, benzene, toluene, pentane, hexane and cyclohexane.

[0016] (4) The present invention provides the method of any one of (1) to (3) above, wherein the amount of the solvent is in the range of 2.5 wt % to 4 wt % based on the total amount of the precursor mixture.

[0017] (5) The present invention provides the method according to any one of (1) to (4) above, wherein the solid electrolyte is a sulfide-based solid electrolyte having an argyrodite-type crystal structure.

[0018] (6) The present invention provides the method according to any one of (1) to (5) above, wherein the sulfide-based solid electrolyte raw material comprises a sulfur precursor, a phosphorus precursor and a LiX precursor, wherein X is a halogen element.

[0019] (7) The present invention provides a method according to any one of (1) to (6) above, wherein the sulfide-based solid electrolyte raw material comprises Li2S, P2S5 and LiX, wherein X is fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).

[0020] (8) The present invention provides a method according to any one of (1) to (7) above, wherein the step (S1) is performed by ball milling the sulfide solid electrolyte raw material and the solvent using a planetary mill containing two zirconium oxide (Zr) balls having different average particle sizes.

[0021] (9) The present invention provides the method according to any one of (1) to (8) above, wherein the precursor mixture prepared in step (S1) is in powder form.

[0022] (10) The present invention provides the method according to any one of (1) to (9) above, wherein the heat treatment temperature in step (S2) is in the range of 350°C to 650°C.

[0023] (11) The present invention provides the method according to any one of (1) to (10) above, wherein the adhesion rate of the precursor mixture heat-treated in the step (S2) calculated by Formula 1 is 1% or less,

[0024] [Formula 1]

[0025] Adhesion rate (%) = (the amount of the precursor mixture powder that adheres to the inner surface of the container after the grinding process and does not fall off when the container is turned upside down after the precursor mixture powder is removed by applying a force of 20 Kgf or less (g) / the total amount of the precursor mixture added to the container (g)) × 100.

[0026] (12) The present invention provides a method according to any one of (1) to (11) above, wherein the solid electrolyte is represented by Formula 1:

[0027] [Formula 1]

[0028] Li a M b P c S d A e

[0029] In formula 1,

[0030] M is at least one element selected from the group consisting of silicon (Si), germanium (Ge), tin (Sn), aluminum (Al), zirconium (Zr), zinc (Zn), arsenic (As), gallium (Ga), antimony (Sb), niobium (Nb), vanadium (V), titanium (Ti), hafnium (Hf), magnesium (Mg), indium (In), copper (Cu), thallium (Tl), lead (Pb), tungsten (W) and nickel (Ni),

[0031] A is at least one element selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and

[0032] 5.5≤a≤7.0, 0≤b≤0.7, 0.3≤c≤1, 4≤d≤5.6 and 0.4≤e≤2.

[0033] (13) The present invention provides a solid electrolyte having a composition represented by Formula 1 and a total impurity content of 1 wt % or less,

[0034] [Formula 1]

[0035] Li a M b P c S d A e

[0036] In formula 1,

[0037] M is at least one element selected from the group consisting of Si, Ge, Sn, Al, Zr, Zn, As, Ga, Sb, Nb, V, Ti, Hf, Mg, In, Cu, Tl, Pb, W and Ni,

[0038] A is at least one element selected from the group consisting of F, Cl, Br and I, and

[0039] 5.5≤a≤7.0, 0≤b≤0.7, 0.3≤c≤1, 4≤d≤5.6 and 0.4≤e≤2.

[0040] (14) The present invention provides the solid electrolyte, wherein the ion conductivity of the solid electrolyte is 5.0 mS / cm or more.

[0041] (15) The present invention provides the solid electrolyte, wherein the electronic conductivity of the solid electrolyte is 1.0×10 -9 mS / cm to 5.0×10 -6 mS / cm.

[0042] Beneficial Effects

[0043] According to the method for preparing a solid electrolyte of the present invention, by using a low-polarity or non-polar solvent that does not have a side reaction with a sulfide solid electrolyte precursor, the generation of hydrogen sulfide gas that has a negative impact on the human body can be prevented during the solid electrolyte preparation process.

[0044] In addition, the method for preparing a solid electrolyte of the present invention can prevent the adhesion of the precursor by using a trace amount of a low-polarity or non-polar solvent during the preparation of the precursor mixture, thereby preventing a decrease in yield, and can alleviate uneven mixing and pulverization of the precursor.

[0045] In addition, since the method for preparing a solid electrolyte of the present invention can reduce the crystallinity of the precursor particles during heat treatment by uniformly grinding and mixing the precursor powders, and can reduce the spacing between the particles, the reactivity of the formation of the solid electrolyte phase can be increased, thereby reducing the phase synthesis temperature during heat treatment, thereby providing a solid electrolyte with reduced impurities and increased ionic conductivity.

[0046] In addition, since the amount of unreacted or side-reacted impurities in the solid electrolyte of the present invention is significantly reduced to increase ion conductivity and reduce electron conductivity, the solid electrolyte of the present invention can improve performance characteristics when used in an all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram illustrating the sequence of the method for preparing a solid electrolyte of the present invention.

[0048] Figure 2 These are photographs showing, for Example 1 and Comparative Example 1, the state of the solid electrolyte present in the container after the solid electrolyte was prepared and the state of the solid electrolyte when transferred to a storage container after the solid electrolyte was prepared. DETAILED DESCRIPTION

[0049] Hereinafter, the present invention will be described in more detail so that the present invention can be more clearly understood. In this case, it should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in the commonly used dictionaries, and it should be understood that the words or terms should be interpreted as having the same meaning as the meaning in the context of the relevant field and the technical idea of ​​the present invention based on the principle that the inventor can appropriately define the meaning of the words or terms to best explain the invention.

[0050] The terms used herein are only for the purpose of describing specific exemplary embodiments and are not intended to limit the present invention.In the present specification, unless otherwise indicated, terms in the singular form may include plural forms.

[0051] It should also be understood that the terms “include,” “comprises,” or “has,” when used in this specification, specify the presence of the features, numbers, steps, elements, or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or a combination thereof.

[0052] The expression 'all-solid-state battery' used in this specification means a battery in which all components of the battery are solid, wherein it is distinguished from a liquid electrolyte secondary battery using a liquid electrolyte such as an electrolytic solution, and a gel polymer secondary battery using a liquid electrolyte while using a polymer electrolyte instead of a separator.

[0053] Method for preparing solid electrolyte

[0054] The method for preparing a solid electrolyte according to the present invention comprises a step (S1) of preparing a precursor mixture by mixing a sulfide-based solid electrolyte raw material and a solvent and a step (S2) of heat treating the precursor mixture. In addition, the relative polarity of the solvent to water is 0.15 or less, and the amount of the solvent may be greater than 2 wt % and less than or equal to 5 wt % based on the total amount of the precursor mixture.

[0055] Figure 1 A schematic diagram illustrating a method for preparing a solid electrolyte according to the present invention is shown. Figure 1 The step (S1) can be performed by preparing a precursor mixture by mixing a powdery precursor of a sulfide-based solid electrolyte with a small amount of a solvent having a relative polarity to water of 0.15 or less and ball-milling the mixture using a planetary mill.

[0056] According to one embodiment of the present invention, the solvent may be at least one selected from the group consisting of xylene, benzene, toluene, pentane, hexane and cyclohexane. The solvent means a solvent having a relative polarity of less than 0.15 to water, wherein the relative polarity refers to the relative polarity of the solvent to water when the polarity of water is 1. That is, a solvent having a relative polarity of less than 0.15 to water means a low polarity or non-polar solvent having a low relative polarity to water. The relative polarity to water may be less than 0.15, less than 0.13, less than 0.11, less than 0.10 and less than 0.08. In the process of preparing a sulfide solid electrolyte, since the sulfide solid electrolyte raw material has a high reactivity with water, it may generate harmful gas hydrogen sulfide when mixed with a polar solvent, but wherein the method for preparing a solid electrolyte of the present invention is mixed with a solvent having a low relative polarity to water, and no side reaction with the sulfide solid electrolyte precursor occurs, so the generation of hydrogen sulfide gas can be suppressed. More specifically, in the method for preparing a solid electrolyte of the present invention, xylene or hexane may be included as a solvent.

[0057] In addition, according to one embodiment of the present invention, the dielectric constant of the solvent may be 4.0 or less. The dielectric constant of the solvent may be 4.0 or less, 3.5 or less, 3.0 or less, 2.5 or less, 2.3 or less, 2.1 or less, 2.0 or less, and 1.9 or less. When the dielectric constant of the solvent satisfies the above range, since the solvent is close to low polarity or non-polarity and does not react with the precursor during the preparation of the solid electrolyte, the generation of hydrogen sulfide gas can be suppressed.

[0058] In addition, according to one embodiment of the present invention, the amount of the solvent may be greater than 2% by weight and less than or equal to 5% by weight, based on the total amount of the sulfide solid electrolyte precursor mixture. Specifically, based on the total amount of the sulfide solid electrolyte precursor mixture, the amount of the solvent may be greater than 2% by weight, more than 2.1% by weight, more than 2.5% by weight, more than 3% by weight, less than 5% by weight, less than 4.5% by weight, less than 4% by weight, less than 3.5% by weight. In the case where the amount of the solvent exceeds the lower limit of the above numerical range, the precursor adhesion problem existing in the solid electrolyte preparation process may not be solved. In addition, it is hoped that the solid electrolyte has low electronic conductivity and high ionic conductivity characteristics, wherein, in the case where the amount of the solvent exceeds the upper limit of the above numerical range, the carbon residue generated by the solvent increases, and due to the carbon residue, the electronic conductivity of the solid electrolyte increases after the drying process and the heat treatment process, so the role of the solid electrolyte that only conducts lithium ions and prevents electrons from moving may be problematic. Specifically, if the electron conductivity of the solid electrolyte increases, side reactions with the positive electrode material in the electrode layer may increase, current efficiency in the solid electrolyte layer may decrease, and problems such as self-discharge or short circuit may occur.

[0059] According to one embodiment of the present invention, the sulfide-based solid electrolyte raw material of the method for preparing a solid electrolyte of the present invention may include a sulfur precursor, a phosphorus precursor and a LiX precursor, wherein X may be a halogen element. Specifically, the sulfide-based solid electrolyte raw material includes Li2S, P2S5 and LiX, wherein X may be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).

[0060] In addition, according to one embodiment of the present invention, the sulfide solid electrolyte may contain lithium, phosphorus, sulfur and halogen elements, and may have an argyrodite-type crystal structure. Since the sulfur ions contained in the sulfide solid electrolyte have a large ion radius, the gap between anions as an ion conduction path is wide, and due to the high polarizability of the sulfur ions, the binding force to the lithium ions is weakened, so the lithium ions can move easily, thereby improving the lithium ion conductivity.

[0061] In addition, in terms of high ionic conductivity and low reactivity with the lithium negative electrode, the sulfide solid electrolyte of the present invention may have a argyrodite-type crystal structure. The sulfide solid electrolyte having an argyrodite-type crystal structure means that the sulfide solid electrolyte has at least a crystalline phase of an argyrodite-type structure as the main phase. In this case, the main phase refers to the phase that accounts for the largest proportion in the total amount of all crystalline phases constituting the sulfide solid electrolyte. Therefore, based on the total crystalline phase constituting the sulfide solid electrolyte, the content ratio of the crystalline phase of the argyrodite-type structure contained in the sulfide solid electrolyte is preferably 80% by weight or more, and may be more preferably 85% by weight or more, 90% by weight or more, or 95% by weight or more.

[0062] In addition, the sulfide-based solid electrolyte may be represented by Formula 1 below.

[0063] [Formula 1]

[0064] Li a M b P c S d A e

[0065] In formula 1,

[0066] M is at least one element selected from the group consisting of silicon (Si), germanium (Ge), tin (Sn), aluminum (Al), zirconium (Zr), zinc (Zn), arsenic (As), gallium (Ga), antimony (Sb), niobium (Nb), vanadium (V), titanium (Ti), hafnium (Hf), magnesium (Mg), indium (In), copper (Cu), thallium (Tl), lead (Pb), tungsten (W) and nickel (Ni),

[0067] A is at least one element selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and

[0068] 5.5≤a≤7.0, 0≤b≤0.7, 0.3≤c≤1, 4≤d≤5.6 and 0.4≤e≤2.

[0069] Generally speaking, if high-energy grinding is performed to mix and crush powders, the powder may be micronized and adhere to the wall. In particular, for sulfide-based solid electrolytes having an argyrodite-type crystal structure, the powder may be unevenly and firmly adhered to the wall before uniform mixing and micronization due to the LiX precursor. In the solid electrolyte preparation process, the key to the solid phase reaction performed by the heat treatment process is to micronize the precursor and mix it uniformly. Only when the precursor is micronized and mixed uniformly can a solid electrolyte with low impurities and uniform composition be prepared. In contrast, in the case of preparing a solid electrolyte by uneven mixing due to adhesion of the precursor powder, the purity and performance of the solid electrolyte may be adversely affected.

[0070] Therefore, the method for preparing a solid electrolyte of the present invention can effectively suppress the adhesion phenomenon and provide an effect of improving the ionic conductivity of the prepared solid electrolyte by adding a trace amount of a solvent with a relative polarity to water of less than 0.15 and mixing them together during the preparation of a sulfide solid electrolyte having a argyrodite-type crystal structure.

[0071] According to one embodiment of the present invention, step (S1) can be performed by ball-milling a sulfide solid electrolyte raw material and a solvent having a relative polarity to water of 0.15 or less using a planetary mill containing two zirconium oxide (Zr) balls having different average particle sizes. Specifically, step (S1) can be performed by adding a sulfur precursor, a phosphorus precursor, and a LiX precursor as sulfide solid electrolyte raw materials into a zirconium oxide container, and stirring and ball-milling by adding two or more ZrO2 balls having different average particle sizes. In addition, the precursor mixture prepared in step (S1) can be in powder form.

[0072] In the case of preparing a solid electrolyte by wet mixing through slurrying or liquefaction, since a part of the solvent remains in the precursor mixture or the solid electrolyte in a carbonized state even after a drying or heat treatment process, a problem of increased electronic conductivity may occur. Therefore, since the method for preparing a solid electrolyte according to the present invention prevents adhesion by dry mixing a sulfide-based solid electrolyte precursor in a powder form and adding a trace amount of a solvent having a relative polarity to water of 0.15 or less, uniform mixing can be induced and the ionic conductivity of the prepared solid electrolyte can be maximized.

[0073] In the ball milling process using a planetary mill, the faster the stirring speed, the faster the formation rate of the solid electrolyte precursor mixture, the smaller the particle size, the longer the stirring time, and the higher the conversion rate to the uniformly mixed solid electrolyte precursor mixture. The stirring time can be more than 3 hours, more than 6 hours, more than 8 hours, more than 10 hours, more than 12 hours, more than 14 hours, more than 24 hours, and the stirring speed can be more than 300 rpm, more than 400 rpm, more than 500 rpm, more than 600 rpm, more than 700 rpm, more than 800 rpm.

[0074] According to one embodiment of the present invention, after step (S1), the heat treatment temperature in step (S2) may be in the range of 350°C to 650°C. More specifically, the heat treatment temperature may be above 300°C, above 350°C, above 450°C, above 500°C, below 650°C, below 600°C, below 550°C. In the case where the heat treatment temperature is within the above range, an argyrodite phase may be formed from the precursor mixture. In particular, in the case of high-energy grinding at 600 rpm or more in step (S1), the precursor mixture in the form of an amorphous powder may be crystallized into an argyrodite solid electrolyte by a heat treatment process.

[0075] In addition, before the heat treatment process, a step of drying the amorphous powdered precursor mixture may be performed. This is to remove the residual solvent in the uniformly mixed precursor mixture, wherein vacuum drying, heat drying or heat drying under vacuum conditions may be performed at room temperature to below 200° C. for 1 minute to 10 hours. Specifically, vacuum drying may be performed using a vacuum oven at a temperature of 80° C. for 1 hour.

[0076] Figure 2 is a photograph showing the state of the solid electrolyte present in the container immediately after the solid electrolyte is prepared and the state of the solid electrolyte when the prepared solid electrolyte is transferred to the storage container for Example 1 and Comparative Example 1. Specifically, Figure 2 (a) shows the state of the solid electrolyte present in the container as a reactor immediately after the solid electrolyte of Example 1 is prepared, wherein it can be confirmed that the solid electrolyte is mixed and present as a uniform powder, and the zirconia balls used are buried in the powder. Figure 2 (b) shows the state of the solid electrolyte in the container as a reactor immediately after the solid electrolyte of Comparative Example 1 was prepared, in which it can be confirmed that the powder adheres to the container wall and the zirconium oxide ball is located in the center of the container. In addition, Figure 2(c) shows the state of the solid electrolyte of Example 1 obtained after the container was turned upside down immediately after the solid electrolyte of Example 1 was prepared, the solid electrolyte powder was transferred to the storage container, and the zirconia balls were separated, wherein it can be confirmed that the solid electrolyte powder did not adhere to the container and was well transferred to the storage container. In addition, Figure 2 (d) shows the state of the storage container obtained after the solid electrolyte of Comparative Example 1 is prepared, the container is immediately turned upside down to transfer it to a storage container, and the zirconia balls are separated, which shows that the solid electrolyte powder is not transferred to the storage container because the solid electrolyte powder adheres to the container wall and the zirconia balls.

[0077] In one embodiment of the present invention, the adhesion rate of the precursor mixture heat-treated in step (S2) calculated by the following formula 1 may be 1% or less,

[0078] [Formula 1]

[0079] Adhesion rate (%) = (the amount (g) of the precursor mixture powder that adheres to the inner surface of the container after the grinding process and does not fall off when the container is turned upside down after the precursor mixture powder is removed by applying a force of 20 Kgf or less / the total amount of the precursor mixture added to the container (g)) × 100.

[0080] The force applied in Formula 1 refers to the instantaneous maximum force applied to the container when using a tool such as a laboratory spoon, a chisel or a rubber mallet or an electric tool. If the force exceeds 20 Kgf, the container may be damaged. In addition, in Formula 1, the grinding process can be a ball milling process using a planetary mill, and can be carried out within the above-mentioned stirring time and stirring speed range. In addition, the container can be one selected from the group consisting of a zirconium oxide container, an agate container, an aluminum oxide container, a silicon nitride container and a tungsten carbide container.

[0081] According to the method for preparing a solid electrolyte of the present invention, when a specific amount of solvent is added and mixed using a planetary mill, since the adhesion rate of the precursor mixture according to Formula 1 is 1% or less, the difficulty of obtaining can be reduced, the yield can be improved, and the ion conductivity of the prepared solid electrolyte can be improved. Specifically, the adhesion rate can be 1% or less, 0.8% or less, 0.6% or less, 0.5% or less, 0.3% or less, 0.2% or less, or 0.1% or less.

[0082] Solid Electrolyte

[0083] The present invention provides a solid electrolyte having a composition represented by the following formula 1 and a total impurity content of 1 wt % or less. The solid electrolyte according to the present invention can be prepared according to various methods for preparing a solid electrolyte, and the above-mentioned method for preparing a solid electrolyte of the present specification can be an example of various methods for preparing a solid electrolyte.

[0084] [Formula 1]

[0085] Li a M b P c S d A e

[0086] In formula 1,

[0087] M is at least one element selected from the group consisting of Si, Ge, Sn, Al, Zr, Zn, As, Ga, Sb, Nb, V, Ti, Hf, Mg, In, Cu, Tl, Pb, W and Ni,

[0088] A is at least one element selected from the group consisting of F, Cl, Br and I, and

[0089] 5.5≤a≤7.0, 0≤b≤0.7, 0.3≤c≤1, 4≤d≤5.6 and 0.4≤e≤2.

[0090] According to the present invention, the solid electrolyte may be a sulfide-based solid electrolyte, and specifically, may be a sulfide-based solid electrolyte having an argyrodite-type crystal structure.

[0091] In addition, the impurities may include unreacted products that are not reacted during the preparation of the solid electrolyte or side reaction products generated by side reactions. Specifically, the impurities may be Li2S or LiA. A in the impurities may be at least one element selected from the group consisting of F, Cl, Br and I. The content of impurities may be obtained by analyzing the X-ray diffraction (XRD) data of the solid electrolyte powder using a Rietveld refinement program.

[0092] The total content of the impurities can be less than 1% by weight. The content of impurities is based on 100% by weight of the solid electrolyte. For example, the content of impurities can be less than 1.0% by weight, less than 0.9% by weight, less than 0.8% by weight, less than 0.7% by weight, less than 0.6% by weight, less than 0.5% by weight, less than 0.4% by weight, less than 0.3% by weight, less than 0.2% by weight, or less than 0.1% by weight. When the content of impurities meets the above range, it can be confirmed that the precursor is micronized and uniformly mixed, and a solid electrolyte with a desired uniform composition can be obtained. In addition, the solid electrolyte prepared by uniform mixing can have high ionic conductivity and low electronic conductivity, and when the solid electrolyte is used in an all-solid-state battery, excellent performance characteristics can be obtained.

[0093] According to one embodiment of the present invention, the ionic conductivity of the solid electrolyte may be 5.0 mS / cm or more. For example, the ionic conductivity may be 5.0 mS / cm or more, 5.1 mS / cm or more, 5.3 mS / cm or more, 5.5 mS / cm or more, 5.7 mS / cm or more, 5.9 mS / cm or more, 6.0 mS / cm or more, 6.1 mS / cm or more, or 6.2 mS / cm or more. Specifically, the ionic conductivity of the solid electrolyte may be 5.9 mS / cm or more.

[0094] In addition, the electronic conductivity of the solid electrolyte can be 1.0×10 -9 mS / cm to 5.0×10 -6 mS / cm. For example, the electronic conductivity of the solid electrolyte can be 1.0×10 -9 mS / cm or more, 2.0×10 -9 mS / cm or more, 5.0×10 -9 mS / cm or more, 7.0×10 -9 mS / cm or more, 9.0×10 -9 mS / cm or more, 1.0×10 -8 mS / cm or more, 2.0×10 -8 mS / cm or more, 5.0×10 -8 mS / cm or more, 7.0×10 -8 mS / cm or more, 9.0×10 -8 mS / cm or more, 1.0×10 -7 mS / cm or more, 1.1×10 -7 mS / cm or more, 1.3×10 -7 mS / cm or more, 1.5×10 -7 mS / cm or more, 1.6×10-7 mS / cm or more, 5.0×10 -6 mS / cm or less, 3.0×10 -6 mS / cm or less, 1.0×10 -6 mS / cm or less, 7.0×10 -7 mS / cm or less, 5.0×10 -7 mS / cm or less, 3.0×10 -7 mS / cm or less, 2.9×10 -7 mS / cm or less, 2.8×10 -7 mS / cm or less, 2.7×10 -7 mS / cm or less, 2.6×10 -7 mS / cm or less. Specifically, the electronic conductivity of the solid electrolyte may be 1.3×10 -7 mS / cm to 2.7×10 -7 The solid electrolyte of the present invention can simultaneously meet the range of ionic conductivity and electronic conductivity. When the range of ionic conductivity and electronic conductivity is met, since the movement of electrons is suppressed and lithium ions are smoothly transferred, an all-solid-state battery with excellent initial efficiency, life characteristics and output characteristics can be provided.

[0095] All-solid-state battery

[0096] The present invention provides an all-solid-state battery comprising the solid electrolyte.

[0097] According to one embodiment of the present invention, the all-solid-state battery comprises a positive electrode, a negative electrode (or no negative electrode) and a solid electrolyte layer comprising a solid electrolyte disposed between the positive electrode and the negative electrode. The ionic conductivity of the all-solid-state battery according to the present invention decreases little, and the electronic conductivity of the solid electrolyte contained is low, so the initial efficiency, life characteristics and output characteristics of the all-solid-state battery can be excellent. In this case, the all-solid-state battery of the present invention can be prepared according to typical methods known in the art. For example, the all-solid-state battery of the present invention can be prepared by stacking and pressing so that a solid electrolyte layer is present between the positive electrode and the negative electrode.

[0098] (1) Positive electrode

[0099] The positive electrode may be prepared by coating a positive electrode collector with a slurry for a positive electrode, the slurry for a positive electrode including a positive electrode active material, a binder, a conductive agent, and a solvent.

[0100] The positive current collector is not particularly limited as long as it has electrical conductivity and does not cause adverse chemical changes in the battery, and stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. Fine irregularities can also be formed on its surface to improve the adhesion strength with the positive active material, and the positive current collector can be used in various shapes such as film, sheet, foil, net, porous body, foam body, non-woven fabric body, etc.

[0101] The positive active material is a compound capable of reversibly inserting and extracting lithium, and specifically, the positive active material may include a lithium metal oxide, and the lithium metal oxide contains lithium and at least one metal such as cobalt, manganese, nickel, or aluminum. More specifically, the lithium metal oxide may include lithium manganese-based oxides (such as LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (such as LiCoO2, etc.), lithium nickel-based oxides (such as LiNiO2, etc.), lithium nickel manganese-based oxides (such as, LiNi 1- Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (such as, LiNi 1-Y1 Co Y1 O2(where 0 < Y1 < 1), etc.), lithium manganese cobalt-based oxides (such as, LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co z1 O4 (where 0 < Z1 < 2), etc.), lithium nickel manganese cobalt-based oxides (such as, Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc.) or lithium nickel cobalt transition metal (M) oxides (such as Li(Ni p2 Co q2 Mn r3 M S2)O2 (where M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg), and molybdenum (Mo), p2, q2, r3, and S2 are the atomic fractions of each independent element, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1, and p2 + q2 + r3 + S2 = 1), etc.), and any one or a mixture of two or more thereof may be included.

[0102] Among these materials, in terms of improving the capacity characteristics and stability of the battery, the lithium metal oxide may be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.) or lithium nickel cobalt aluminum oxide (e.g., LiNi 0.8 Co 0.15 Al 0.05 O2, etc.). Considering the significant improvement effect brought about by controlling the type and content ratio of the elements constituting the lithium composite metal oxide, the lithium composite metal oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, and any one or a mixture of two or more thereof may be used.

[0103] Based on the total weight of the solid components excluding the solvent in the positive electrode paste, the content of the positive electrode active material may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 99% by weight or less, 98% by weight or less.

[0104] The binder is a component that helps the conductive agent, the active material and the current collector to adhere to each other. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0105] The binder may be generally contained in an amount of 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of solid components excluding the solvent in the positive electrode slurry.

[0106] The conductive agent is a component for further improving the conductivity of the positive electrode active material.

[0107] The conductive agent is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, conductive materials such as graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.

[0108] The content of the conductive agent may generally be 1 wt % or more, 20 wt % or less, 15 wt % or less, or 10 wt % or less, based on the total weight of the solid components excluding the solvent in the positive electrode slurry.

[0109] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and its amount may be such that a desired viscosity is obtained when the positive electrode active material and the optional binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solid component containing the positive electrode active material and the optional binder and the conductive agent is 50% by weight or more, 60% by weight or more, 70% by weight or more, 95% by weight or less, 90% by weight or less, or 85% by weight or less.

[0110] (2) Negative electrode

[0111] The negative electrode can be prepared, for example, by coating a negative electrode slurry on a negative electrode current collector, the negative electrode slurry containing a negative electrode active material, a binder, a conductive agent and a solvent, or a graphite electrode formed of carbon (C) or lithium metal itself having a thickness of 50 μm or less can be used as the negative electrode, or as a non-negative electrode type, it may not contain a negative electrode.

[0112] For example, in the case where the negative electrode is prepared by coating the negative electrode slurry on the negative electrode collector, the thickness of the negative electrode collector is generally 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery, and can be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. In addition, similar to the positive electrode collector, the negative electrode collector may have fine surface concavoconvexities to improve the bonding strength with the negative electrode active material, and the negative electrode collector may be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0113] The negative electrode active material may include at least one negative electrode active material selected from the group consisting of natural graphite, artificial graphite, carbonaceous materials; lithium-containing titanium composite oxide (LTO), Si, SiO x , metal (Me) such as Sn, lithium (Li), Zn, Mg, cadmium (Cd), cerium (Ce), Ni or Fe; alloy composed of metal (Me); oxide (MeO x ); and a composite material of metal (Me) and carbon. Specifically, a composite material including silicon (Si), silicon oxide (SiO x ) or a silicon-based negative electrode active material of a silicon alloy as the negative electrode active material. In this case, since a thin and stable SEI layer containing a siloxane bond is formed, the high temperature stability and life characteristics of the battery can be further improved.

[0114] The negative electrode active material may be contained in the negative electrode slurry in an amount of 60 wt % or more, 70 wt % or more, 80 wt % or more, 99 wt % or less, or 98 wt % or less based on the total weight of solid components excluding the solvent in the negative electrode slurry.

[0115] The binder is a component that helps the conductive agent, the active material and the current collector to adhere to each other. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0116] The content of the binder may generally be 1 wt % or more, 20 wt % or less, 15 wt % or less, or 10 wt % or less, based on the total weight of the solid content excluding the solvent in the negative electrode slurry.

[0117] The conductive agent is a component for further improving the conductivity of the negative electrode active material. The conductive agent is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, for example, conductive materials such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0118] The content of the conductive agent may be 1 wt % or more, 20 wt % or less, 15 wt % or less, or 10 wt % or less, based on the total weight of the solid components excluding the solvent in the negative electrode slurry.

[0119] The solvent may include water or an organic solvent, such as NMP (N-methyl-2-pyrrolidone), and its amount may be such that a desired viscosity is obtained when the negative electrode active material and the optional binder and the conductive agent are included. For example, the content of the solvent may be such that the concentration of the solid component including the negative electrode active material and the optional binder and the conductive agent is 50% by weight or more, 60% by weight or more, 70% by weight or more, 95% by weight or less, 90% by weight or less, or 85% by weight or less.

[0120] In the case where the metal itself is used as the negative electrode, the negative electrode may be a metal film itself, or may be prepared by physically bonding, rolling or depositing the metal on the negative electrode current collector. As a deposition method, an electrodeposition method or a chemical vapor deposition method for the metal may be used.

[0121] For example, the metal film itself or the metal to be bonded / rolled / deposited on the negative electrode current collector may contain one metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two metals.

[0122] (3) Solid electrolyte layer

[0123] In addition to the solid electrolyte according to the present invention, the solid electrolyte layer may further include a binder.

[0124] The binder is a component that helps the solid electrolyte particles to adhere to each other. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0125] The content of the binder may be 0.1 wt % or more, 5 wt % or less, 3 wt % or less, or 2 wt % or less, based on the total weight of the solid electrolyte layer.

[0126] The present invention provides a battery module including the all-solid-state battery as a unit cell, and can provide a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0127] Hereinafter, embodiments of the present invention will be described in detail in a manner that a person skilled in the art can easily carry out the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments described herein.

[0128] Examples and Comparative Examples

[0129] Example 1

[0130] Li2S powder, P2S5 powder and LiCl powder are used as raw material powders. After weighing, the composition of these powders is Li6PS5Cl, and the total weight is 5 g. A total of 30 g of ZrO2 balls (zirconia balls, 15 g each) with a diameter of 5 mm and 10 mm are added to a 45 ml ZrO2 (zirconia) container at a ratio of 1:1, and then 5 g of raw material powder and 0.125 g of xylene (2.5% by weight based on the total precursor powder content) are added together. Using a high-energy ball milling device (equipment name: Pulverisette 7premium, FRITSCH company), ball milling is performed at 400 rpm for 3 hours by a planetary mill, and the powder material composed of Li6PS5Cl obtained by ball milling is dried for 2 hours in a vacuum oven at 80 ° C. Thereafter, heat treatment is performed again at 550 ° C for 12 hours to obtain a solid electrolyte powder material.

[0131] Example 2

[0132] The same procedure as in Example 1 was carried out, but 0.2 g of xylene (4 wt % based on the total precursor powder content) was added.

[0133] Example 3

[0134] The same procedure as in Example 1 was performed, but 0.125 g of hexane (2.5 wt % based on the total precursor powder content) was added.

[0135] Comparative Example 1

[0136] The same procedure as in Example 1 was followed, but without the addition of xylene.

[0137] Comparative Example 2

[0138] The same procedure as in Example 1 was carried out, but 0.075 g of xylene (1.5 wt % based on the total precursor powder content) was added.

[0139] Comparative Example 3

[0140] The same procedure as in Example 1 was performed, but 0.075 g of hexane (1.5 wt % based on the total precursor powder content) was added.

[0141] Comparative Example 4

[0142] The same procedure as in Example 1 was carried out, but 0.3 g of xylene (6 wt % based on the total precursor powder content) was added.

[0143] Comparative Example 5

[0144] The same procedure as in Example 1 was carried out, but 0.125 g of tetrahydrofuran (2.5 wt % based on the total precursor powder content) was added.

[0145] Experimental Example 1

[0146] Adhesion rate measurement: In the above-mentioned embodiments and comparative examples, after measuring the total amount of solid electrolyte powder material added to the zirconia container, ball milling was performed by a planetary mill, and then the amount of solid electrolyte powder that could be removed by applying a pressure of 20 Kgf without damaging the zirconia container using a tool such as a laboratory spoon was measured to calculate the ratio of the amount of powder adhering to the inner surface of the container to the total amount of the solid electrolyte powder material.

[0147] Experimental Example 2

[0148] Ion conductivity measurement: 150 mg of the solid electrolyte prepared in the embodiment and the comparative example, i.e., Li6PS5Cl, was added to a mold with a diameter of Φ 13 mm, and then a pressure of 370 MPa was applied to form a solid electrolyte layer. The ionic conductivity was measured at room temperature (25°C) using a potentiostat (Biologic, SP-200) with an amplitude of 10 mV and a measurement frequency range of 0.1 Hz to 7 MHz.

[0149] Experimental Example 3

[0150] Impurity ratio measurement: The impurity ratio of the solid electrolyte powder was calculated using X-ray diffraction (XRD) measurement and Rietveld refinement analysis. Bruker's D8 Endeavor with Cu Kα radiation at a wavelength of 1.5406 Å was used as the XRD equipment, with a scanning rate of 2° / min and a 2θ angle of 10° to 90° and non-atmospheric exposure as measurement conditions. The impurities were identified using the TOPAS Rietevld refinement program, and the impurity ratio was quantified.

[0151] Experimental Example 4

[0152] Electronic conductivity measurement: 150 mg of the solid electrolyte Li6PS5Cl prepared in the examples and comparative examples was added to a mold with a diameter of Φ 13 mm, and then a pressure of 370 MPa was applied to form a solid electrolyte layer. Then, 1 V DC was applied for 6 hours at room temperature (25°C) using a potentiostat (Biologic, SP-200) to saturate the current so that the current did not change. Then, the electronic conductivity was measured by measuring the current value.

[0153] The adhesion rate, ion conductivity, impurity ratio, and electron conductivity measured by Experimental Examples 1 to 4 are shown in Table 1 below.

[0154]

[0155] Referring to Table 1, it can be confirmed that by adding a trace amount of a solvent having a relative polarity to water of 0.15 or less, Examples 1 to 3 have very low adhesion rates and impurity ratios, and have excellent solid electrolyte properties due to high ion conductivity and low electron conductivity. Figure 2 , for Example 1, it can be confirmed that the precursor mixture was prepared by uniformly mixing the precursors, and it can be confirmed that only 0.2% of the powder adhered to the container. In contrast, it can be confirmed that Comparative Example 1, which did not use a solvent, had a very high adhesion rate and impurity ratio, and accordingly, it can be confirmed that the ion conductivity of the solid electrolyte thus prepared was low, and thus the performance was degraded. Reference Figure 2, for Comparative Example 1, it can be confirmed that 99.9% of the powder in the prepared precursor mixture adheres to the container and is not transferred to the storage container. It can also be confirmed that Comparative Examples 2 to 4, in which the solvent used exceeds the solvent content range of the present application, have very poor adhesion and / or impurity ratios, and in addition, have low ionic conductivity. In particular, since Comparative Example 4 has a low ionic conductivity value and a high electronic conductivity value, it can be confirmed that it is not suitable for use as a solid electrolyte. In addition, tetrahydrofuran has a strong polarity, wherein, for Comparative Example 5 in which tetrahydrofuran is added as a solvent instead of a solvent having a relative polarity to water of less than 0.15, it can be confirmed that it is not suitable for use as a solid electrolyte due to a high impurity ratio, a low ionic conductivity value, and a high electronic conductivity value.

Claims

1. A method for preparing a solid electrolyte, the method comprising the following steps: preparing a precursor mixture (S1) by mixing a sulfide-based solid electrolyte raw material and a solvent; and thermally treating the precursor mixture (S2), wherein the relative polarity of the solvent to water is less than 0.15, and The amount of the solvent is greater than 2 wt % and less than or equal to 5 wt % based on the total amount of the precursor mixture. The method according to claim 1 , wherein the dielectric constant of the solvent is 4.0 or less. 3 . The method according to claim 1 , wherein the solvent is at least one selected from the group consisting of xylene, benzene, toluene, pentane, hexane, and cyclohexane. 4 . The method according to claim 1 , wherein the amount of the solvent is in the range of 2.5 wt % to 4 wt % based on the total amount of the precursor mixture. 5 . The method according to claim 1 , wherein the solid electrolyte is a sulfide-based solid electrolyte having an argyrodite-type crystal structure. 6 . The method according to claim 1 , wherein the sulfide-based solid electrolyte raw material comprises a sulfur precursor, a phosphorus precursor, and a LiX precursor, wherein X is a halogen element.

7. The method according to claim 1, wherein the sulfide-based solid electrolyte raw material comprises Li2S, P2S5 and LiX, wherein X is chlorine (Cl), bromine (Br) or iodine (I).

8. The method according to claim 1, wherein the step (S1) is performed by ball-milling the sulfide-based solid electrolyte raw material and the solvent using a planetary mill containing two types of zirconium oxide (Zr) balls having different average particle sizes.

9. The method according to claim 1, wherein the precursor mixture prepared in the step (S1) is in a powder form.

10. The method according to claim 1, wherein the heat treatment temperature in the step (S2) is in the range of 350°C to 650°C.

11. The method according to claim 1, wherein the adhesion rate of the precursor mixture heat-treated in the step (S2) calculated by Formula 1 is 1% or less, [Formula 1] Adhesion rate (%) = (the amount of the precursor mixture powder that adheres to the inner surface of the container after the grinding process and does not fall off when the container is turned upside down after the precursor mixture powder is removed by applying a force of 20 Kgf or less (g) / the total amount of the precursor mixture added to the container (g)) × 100.

12. The method according to claim 1, wherein the solid electrolyte is represented by Formula 1, [Formula 1] Li a M b P c S d A e in, In formula 1, M is at least one element selected from the group consisting of silicon (Si), germanium (Ge), tin (Sn), aluminum (Al), zirconium (Zr), zinc (Zn), arsenic (As), gallium (Ga), antimony (Sb), niobium (Nb), vanadium (V), titanium (Ti), hafnium (Hf), magnesium (Mg), indium (In), copper (Cu), thallium (Tl), lead (Pb), tungsten (W) and nickel (Ni), A is at least one element selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and 5.5≤a≤7.0, 0≤b≤0.7, 0.3≤c≤1, 4≤d≤5.6 and 0.4≤e≤2.

13. A solid electrolyte having a composition represented by Formula 1, and Total impurity content is less than 1% by weight: [Formula 1] Li a M b P c S d A e in, In formula 1, M is at least one element selected from the group consisting of silicon (Si), germanium (Ge), tin (Sn), aluminum (Al), zirconium (Zr), zinc (Zn), arsenic (As), gallium (Ga), antimony (Sb), niobium (Nb), vanadium (V), titanium (Ti), hafnium (Hf), magnesium (Mg), indium (In), copper (Cu), thallium (Tl), lead (Pb), tungsten (W) and nickel (Ni), A is at least one element selected from the group consisting of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and 5.5≤a≤7.0, 0≤b≤0.7, 0.3≤c≤1, 4≤d≤5.6 and 0.4≤e≤2. 14 . The solid electrolyte according to claim 13 , wherein the solid electrolyte has an ion conductivity of 5.0 mS / cm or more.

15. The solid electrolyte according to claim 13, wherein the electronic conductivity of the solid electrolyte is 1.0×10 -9 mS / cm to 5.0×10 -6 mS / cm.

Citation Information

Patent Citations

  • Sulfide-based solid electrolyte having high ion conductivity in a wide crystalization temperature range and preparation method thereof

    KR1020180057423A

  • Drive control device and drive control method, and program

    KR1020220117224A